التأصيل السياسي والاجتماعي لقيمة التسامح بالجزائر - فاضل, أمال (جامعة الوادي University of Eloued, 2019)
تسعى هذه الورقة البحثية إلى معالجة كيفية توظيف السلطة السياسية في الجزائر لقيمة التسامح من أجل معالجة أزمة متعددة الأبعاد، هزت أركن الدولة الجزائرية خلال الفترة الممتدة من سنتي 1992 و2006. وبحكم أن التسامح هو قيمة دينية مستوحاة من الإسلام، كما أنها راسخة في العادات والتقاليد الجزائرية، لم يكن من الصعب على السلطة توظيف هذه القيمة لتمرير قانون المصالحة الوطنية، والذي دعت من خلاله أفراد المجتمع الجزائري إلى التسامح فيما بينهم، والعمل على العيش سويا دون النظر إلى الانتماء الجهوري. وقد اعتمدت في ذلك على آليات عديدة منها المؤسسات التربوية من خلال إدراج التسامح في المقررات الدراسية لجميع الأطوار، وكذا وسائل الإعلام العمومية خاصة التلفزيون الجزائري للترويج لهذه القيمة المجتمعية واخيرا توظيف المساجد من خلال توجيه الخطب الدينية لحث الجزائريين على اعتماد هذه القيمة. This paper seeks to address how the political authority of Algeria is used to value tolerance in response to multidimensional crisis that shook the Algerian state during the period from 1992 to 2006. Since tolerance is a religious value inspired by Islam and firmly rooted in Algerian customs and traditions, it was not difficult for the Authority to use this value to pass the National Reconciliation Act, in which the members of Algerian society called for tolerance among themselves and to live together without regard to their regional affiliations. It has relied on several mechanisms, including educational institutions, through the inclusion of tolerance into curricula at all levels, as well as the public media, especially Algerian television, to promote this social value and finally to employ mosques by directing religious sermons to urge Algerians to adopt this value.
Political And Social Consolidation Of The Value Of Tolerance In Algeria
Keywords: التسامح ; المصالحة ; الرحمة ; المسجد ; المدرسة; Tolerance ; Reconciliation ; Mercy ; The Mosque ; School